Pelatihan Menumbuhkan Jiwa Kewirausahaan di Kalangan Ibu Rumah Tangga di Kelurahan Lembah Alas Kutacane - Tri Rasid Desky (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The economic crisis has made this nation aware of the importance of the role of MSMEs in the Indonesian economy. The MSME economy is a mainstay and a choice for many people, especially graduates, to live more prosperously and independently. It also helps many people overcome unemployment. Seeing the added value of MSMEs above, the entrepreneurial spirit should be introduced and fostered among housewives. If they have insight into entrepreneurship, it is likely that these mothers will pioneer into becoming entrepreneurs by seeing the opportunities around them. That way, they can use their time more positively and explore their potential optimally. So that they will have more productive activities in their spare time after taking care of the household. Mothers who have a side business that can be done at home are expected to be more prosperous because there is additional income. This means that family welfare also increases. Implementation, the activity was carried out in the Lembah Alas Kutacane Village on Saturday, April 27, 2024. Furthermore, socialization was given by the community service team of the Lembah Alas Kutacane Village regarding. This counseling activity was attended by approximately 45 participants from the community of Lembah Alas Kutacane Village. The counseling participants looked enthusiastic about the materials presented by the speakers and were able to actively participate, so that this counseling activity took place with a two-way system and many participants asked questions. The presentation of the counseling material was followed by a discussion, ice breaking, and the distribution of door prizes to participants who were active during the discussion activity.